Low-energy electrons transform the nimorazole molecule into a radiosensitiser - Meißner, Rebecca (2020)
This work was supported by FWF, Vienna (P30332). R.M. and P.L.V. acknowledge the Portuguese National Funding Agency FCT-MCTES through PD/BD/114452/2016 and research grants UID/FIS/00068/2019 (CEFITEC) and PTDC/FIS-AQM/31281/2017. This work was also supported by Radiation Biology and Biophysics Doctoral Training Programme (RaBBiT, PD/00193/2010); UID/Multi/04378/2019 (UCIBIO). J.K. acknowledges the support by the Czech Science Foundation Grant 19-01159S. L.F. is grateful to the LABEX Lyon Institute of Origins (ANR-10-LABX-0066) of the Universite de Lyon for its financial support within the program "Investissements d'Avenir" (ANR-11-IDEX-0007) of the French government operated by the National Research Agency (ANR).